2019
DOI: 10.1002/arch.21650
|View full text |Cite
|
Sign up to set email alerts
|

Development of efficient RNAi in Nezara viridula for use in insecticide target discovery

Abstract: Stink bugs are an emerging pest in many regions of the world but their molecular biology is still poorly understood.While several transcriptomes are available, the lack of validated gene manipulation tools like RNA interference (RNAi) in species such as the southern green stinkbug Nezara viridula precludes the characterization of individual genes in vivo. Such tools are particularly useful in performing high-throughput screens to search for essential genes that can be prioritized as potential insecticide targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Also, we identified suitable target genes for oral delivery. Previously, the core genes of the RNAi mechanism were found to be expressed in N. viridula, 33 and more recently, Riga et al 29 have demonstrated RNAi functionality by microinjection of gene-specific dsRNA in this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we identified suitable target genes for oral delivery. Previously, the core genes of the RNAi mechanism were found to be expressed in N. viridula, 33 and more recently, Riga et al 29 have demonstrated RNAi functionality by microinjection of gene-specific dsRNA in this species.…”
Section: Discussionmentioning
confidence: 99%
“…28 In SGSB, recently, it has been demonstrated that microinjection-mediated delivery of dsRNA targeting essential genes led to significant mortality in the nymphs. 29 The main objectives of this study were to first identify suitable target genes for oral delivery and then to evaluate the RNAi response of SGSB to orally delivered dsRNA. It is critical to identify the RNAi efficacy of orally delivered dsRNA in order to develop biopesticides based on this technology.…”
Section: Introductionmentioning
confidence: 99%
“…Post-transcriptional gene silencing also known as RNA interference (RNAi) was first elucidated in 1998 [5] and has since then been widely used as a tool in the study of gene function. In the hemipteran group, RNAi has been used to study the role of genes in insect development/reproduction of several species, such as Oncopeltus fasciatus [6,7], Nezara viridula ( [8], Diaphorina citri [9], Halyomorpha halys [10], among others. RNAi is a highly conserved mechanism among eukaryotic organisms, in which the messenger RNA (mRNA) is cleaved by the RNAi machinery, leading to the inactivation of gene expression [11].…”
Section: Introductionmentioning
confidence: 99%
“…Hemiptera genes have been successfully silenced through this method (Christiaens & Smagghe, 2014;Bansal et al, 2016;Ghosh et al, 2017;Lu et al, 2017;Mogilicherla et al, 2018, Riga et al, 2019.…”
Section: Discussionmentioning
confidence: 99%